Calculation of deflections of hollow concrete-filled steel tubular members of three-hinge suspension structure/Kabamosios trilankstės betonšerdžzių tuščiavidurių vamzdinių plieno strypų konstrukcijos įlinkių skaičiavimas - Šaraškinas, Viačeslavas; Kvedaras, Audronis Kazimieras (Journal of Civil Engineering and Management, 2001)
Recently, in scientific literature, information on a new type of suspended straight-line 3-hinged roof structures has considerably increased. It was stressed that straight-line elements are easily manufactured and erected, roof decking service conditions are good. In the world building practice during last 30 years very effective composite structures have been introduced, even hollow concrete-filled steel tubular members. But no information on the application of such members for suspended roofs was obtained. In some sources very simple straight-line suspended roofs structures were analysed, and for those shapes an effective centrifuged hollow concrete-filled steel tubular members may be successfully applied. These members do not require additional roof stabilisation. These composite ropes may be attributed to the elements of final flexural stiffness, and they are effective and simple to decrease deflections of the suspended roof. However, for these composite ropes the methods of their deflection calculations must be developed because it is necessary to estimate their composite cross-section and interaction between components. This paper deals with analysis of these ropes’ behaviour and their deflection calculation, which was made by exact I. Kalminzer’s and other simplified methods. The vertical deflections in the middle of elements of the straight-line three-hinge composite suspended structure may be calculated as consisting of two parts depending on their bending and tension. The part of vertical deflection at mid-span of a composite member connected with its bending may be calculated as for hollow concrete-filled steel tubular beam taking into account the sum of flexural bending stiffness of its cross-sectional components (EJ)c . The I.Kalminzer’s or other simplified methods taking into account the sum of flexural bending stiffness of cross-sectional components may calculate the vertical deflection called by tension of element as the member of final flexural stiffness (EJ)c . Comparison of experimental and theoretical data shows a good satisfaction when deflection calculation for the straight-line composite rope is made by dividing it into two parts depending on bending and tension. Investigation made into the deformation properties and methods of deflection definition of straight-line circular hollow concrete-filled steel tubular members allows declaring the possibility of useful application of such members as the ones of final flexural stiffness in suspended roof structures. Article in Lithuanian. First Published Online: 30 Jul 2012